Heinous crime : cases, causes, and consequences - Reamer, Frederic G., 1953- (Columbia University Press, 2005)
Annotation What circumstances lead someone to commit murder, rape, or acts of child molestation? Why does society have such a deep-seated wish for vengeance against perpetrators of heinous crimes? Can those found guilty of such crimes ever be rehabilitated? Officials of the criminal justice system, politicians, and ordinary citizens argue about possible solutions to these controversial and vital questions, with little argeement. This book offers innovative perspectives on the difficult issues concerning a civilized society's response to offenders guilty of heinous crimes. Reamer critiques current practices of punishment, drawing on his extensive experience as a member of the Rhode Island Parole Board, where he has heard more than 13,000 cases, and as a social worker in correctional facilities. He examines the psychological and social factors that lead individuals to commit reprehensible crimes and discusses specific strategies for prevention and treatment. He considers the effectiveness and rationale of responses to heinous crimes, including revenge and retribution, imprisonment for public safety, rehabilitation, and restorative justice.